Integrated Approach to the Auto-Ecological Study of Presence of Brassica Incana Ten. in the Gargano (Puglia, southern Italy), on the Adriatic side of the Italian Peninsula (Global Journal of Science Frontier Research, 2021)
The study deals with the finding of new localities of Brassica incana Ten. in the Gargano promontory; B. incana is a species of the European flora occurring in Italy and in the Balkan area, assessed as Data Deficent (DD) according to IUCN criteria. The presence of the species in Apulia was based on old records not recently confirmed. The new Gargano's finds are limited to the imposing and inaccessible cliff of Monte Pucci, a small promontory placed on the coast between Rodi Garganico and Peschici (FG). B. incana grows on the edge of small terraces of the cliff with other typical rupicolous plants such as Matthiola incana, Anthyllis barba-jovis, Allium commutatum, Campanula garganica, Capparis rupestris subsp. rupestris and Brachypodium retusum. Geological and pedological analyses have detected the stratigraphic units that form the substratum of B. incana habitat (Scaglia formation-Upper Cretaceous-; Peschici formation-Middle Eocene), which turn out to be unique in the Gargano promontory. Based on these data, the study shows that B. incana is linked to specific geological and pedological substrates (soils rich of SiO2).
Keywords: chasmophytic vegetation; distribution range; rock stratigraphy; species auto ecology